The Role of Understanding the Medicolegal Implications of Occupational Safety and Health (OSH): An Observational Study of Compliance with the Use of Personal Protective Equipment (PPE) among Single Center Laboratory Staff at Indriati Boyolali Hospital - Putri, Arum Kusuma; Ilyas Syafiq Darul Ridzuan; Emma Ismawatie; Yulita Maulani; Basuko Agus Wibowo (Phlox Institute: Indonesian Medical Research Organization, 2024)
Introduction: Occupational safety and health (OSH) is a crucial issue in the medical laboratory environment, considering the potential for exposure to various biological and chemical risks. The proper use of personal protective equipment (PPE) is one of the main pillars in mitigating this risk. Understanding the medicolegal implications related to the use of PPE is an important aspect that can influence laboratory staff compliance. This study aims to examine the relationship between understanding medicolegal implications and compliance with the use of PPE among laboratory staff at Indriati Boyolali Hospital. Methods: This study used a cross-sectional observational design. The sample consisted of 120 laboratory staff at Indriati Boyolali Hospital who were selected randomly. Data was collected through structured questionnaires to measure the level of understanding of medicolegal implications and direct observation to assess compliance with PPE use. Data analysis was carried out using descriptive and inferential statistical tests (chi-square test and logistic regression). Results: The research results showed that there was a significant relationship between understanding medicolegal implications and compliance with PPE use (p < 0.05). Laboratory staff with a better understanding of medicolegal implications tend to demonstrate higher levels of compliance in the use of PPE. Other factors such as age, gender, and work experience were also found to influence compliance with PPE use. Conclusion: Understanding medicolegal implications is an important factor that contributes to compliance with the use of PPE among laboratory staff. Comprehensive educational interventions regarding medicolegal aspects of OSH can increase the understanding and awareness of laboratory staff, thereby contributing to improving occupational safety and health in the laboratory environment.